2022
DOI: 10.1186/s12870-022-03597-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mepiquat chloride (DPC) on the soluble protein content and the activities of protective enzymes in cotton in response to aphid feeding and on the activities of detoxifying enzymes in aphids

Abstract: Background Mepiquat chloride (DPC) enhances the resistance of cotton plants, and it is widely used as a growth regulator. DPC can stimulate photosynthesis, stabilize the structure of cotton leaves, and affect population reproduction and energy substances in Aphis gossypii Glover (cotton aphids), but interactions between DPC and cotton aphids remain unclear. In this study, we analyzed the physiological responses of cotton to DPC, and the toxicity of DPC toward cotton aphids, before and after fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…When cucumber plants are damaged by the leaf miner Liriomyza huidobrensis, the can adapt to insect stress by regulating the main nutrients, secondary metabolites, chlorophyll content, and defensive enzyme activity (Sun et al, 2012(Sun et al, , 2013. In our previous studies, we found that cotton aphid feeding can also cause changes in the photosynthetic capacity, nutrient levels, metabolic pathways, protective enzyme activities, and other defense mechanisms in the host cotton plants (Zhang et al, 2020, Zhang Q. C. et al, 2022a. In this study, we found that when only infected with powdery mildew, the cucumber plants were able to resist the powdery mildew pathogen by increasing the soluble protein and soluble sugar contents, and regulation the activities of protective enzymes, but the response of protective enzymes is not so intense (Figures 1, 2A,B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When cucumber plants are damaged by the leaf miner Liriomyza huidobrensis, the can adapt to insect stress by regulating the main nutrients, secondary metabolites, chlorophyll content, and defensive enzyme activity (Sun et al, 2012(Sun et al, , 2013. In our previous studies, we found that cotton aphid feeding can also cause changes in the photosynthetic capacity, nutrient levels, metabolic pathways, protective enzyme activities, and other defense mechanisms in the host cotton plants (Zhang et al, 2020, Zhang Q. C. et al, 2022a. In this study, we found that when only infected with powdery mildew, the cucumber plants were able to resist the powdery mildew pathogen by increasing the soluble protein and soluble sugar contents, and regulation the activities of protective enzymes, but the response of protective enzymes is not so intense (Figures 1, 2A,B).…”
Section: Discussionmentioning
confidence: 99%
“…After applying pesticides, the desired outcome is to reduce the occurrence of pests and diseases and to alleviate the stress on the plants. However, our latest research shows that mepiquat chloride (DPC), a plant growth regulator, not only has toxic effects on cotton aphids ( A. gossypii ), but also enhances the defense response of cotton plants against cotton aphids ( Zhang Q. C. et al, 2022a ). In this study, we also found that both azoxystrobin and imidacloprid treatment increased chlorophyll ( Figures 9A , 11A ), soluble protein ( Figures 10A , 12A ), and free proline contents ( Figures 10C , 12C ), and increased SOD activity ( Figures 9B , 11B ) and decreased MDA content ( Figures 10D , 12D ) in cucumber leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we believe that when controlling S. planiculmis , application of low-dose selective herbicides may help cotton to resist stress caused by weeds. Our previous studies showed that application of low-dose insecticides, fungicides and plant growth regulators can increase protective enzyme activities of cotton, and help resist pest-associated stress ( Zhang et al., 2022c ; Zhang et al., 2022d ; Zhang et al., 2022e ). Clearly, a low-dose pesticide can stimulate the defence response of cotton.…”
Section: Discussionmentioning
confidence: 99%
“…These exogenous hormones can usually promote seed germination, seedling growth and development, increase the content of osmotic adjustment substances in leaves, antioxidant enzyme activity and chlorophyll content, reduce the relative conductivity and malondialdehyde content of seedling leaves, thereby improving the drought resistance of crops ( Arnao and Hernández-Ruiz, 2018 ; Ahmad et al., 2023 ; Liu et al., 2023 ). Some plant growth regulators, such as mepiquat chloride, are commonly used to regulate cotton plant type, but can also increase soluble protein content and antioxidant enzyme activity ( Zhang et al., 2022d ). It can also promote the accumulation of flavonoids in soybeans to enhance drought resistance ( Figure 3 ) ( Wang et al., 2023a ).…”
Section: Methods To Improve Drought Tolerancementioning
confidence: 99%